KNOWLEDGE AND PERCEPTION OF LIBERIAN AGRIBUSINESSES IN THE AFRICAN CONTINENTAL FREE TRADE AREA (AfCFTA) - Ninson, Jacqueline; Aidoo, Andrews; Brobbey, Maame Kyerewaa (Applied Studies in Agribusiness and Commerce, 2024)
Liberia has signed and ratified AfCFTA and is pending deposit with the African Union Commission. The objective of the paper thus is to examine the knowledge, and perception of Liberian agribusinesses on AfCFTA. The primary data were obtained from four (4) main categories of stakeholders in Liberia’s economic growth and development. They included (i) agribusiness enterprises/agricultural micro-small- and medium-sized enterprises operating in Monrovia; (ii) apex business entities/associations; (iii) government actors and (iv) partnerships in trade and development in Liberia. Findings from engagements with agribusinesses revealed that even though few respondents had a fair understanding of the Rules of Origin protocol, central to trading under AfCFTA, most of the respondents knew or had heard about the AfCFTA and mostly associated AfCFTA with creating one African market. Concentration on AfCFTA in Liberia should not only be on the removal of tariffs as the removal of tariffs is perceived by agribusiness as bad.